THE STUDENTS' MOTIVATION IN LEARNING ENGLISH FROM HOME AT SMA NEGERI 3 LUWU - Afrilia AS; St Asriati AM; Ariana (FKIP Unismuh Makassar, 2022)
This study aimed to determine The Students' Motivation in Learning English From Home. The method of this research was the descriptive qualitative method. Data for the research was collected through interviews (semi-structured interviews) with WhatsApp (WA) as a data collection tool.The sample for this research was students of class XI IPA SMA Negeri 3 Luwu. Samples were taken using the purposive sampling technique.Based on the results of the study, the researchers found that learning English from home makes students tend to be lazy and their learning motivation decreases because it is influenced by extrinsic motivation, such as the environment, teachers, and parents.In the environment part, conditions at home cause a lot of disturbances when starting the lesson, whether it's the sound of chickens, television, car horns, or the sound of motorcycles that interfere.In the teacher part, the teacher is an important factor in aspiring for the implementation of these functions by meeting the needs of students. These needs include physiological needs, the need for safety and security, the need to be accepted and loved, the need for self-esteem, and the need for self-realization.In the parents part, lack of parental attention when studying from home means that learning interest is reduced. Parents who are busy with their work make their children feel neglected. This condition certainly requires parents and families to accompany children, especially in the learning process. The active role of parents and families in children's education, especially during the pandemic, is very important, especially since the role of teachers and educational institutions is more limited in scope. There is a very close and significant relationship between online learning and student learning motivation. Learning motivation was very influential on learning from home.